Joint Auditing and Modern Technological Environment in Auditor Report Quality - Ali Mahmood Ahmed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Joint auditing has emerged as a critical response to environmental changes in the business landscape, aiming to enhance professional performance and increase stakeholder confidence in financial reporting through collaborative audit approaches. Specific Background: The practice involves two or more independent auditors sharing audit responsibilities and jointly issuing a single audit report, while modern technological environments have introduced new dimensions to audit quality through electronic reporting systems and digital assurance services. Knowledge Gap: Despite recognition of joint auditing's potential benefits, limited empirical evidence exists regarding how the integration of joint auditing practices with elements of modern technological environments specifically enhances the quality of auditors' reports in public sector institutions. Aims: This research examines the relationship between joint auditing mechanisms and modern technological environmental elements in improving auditor report quality at the Federal Board of Supreme Audit, analyzing data from 2015 to 2024 using econometric modeling. Results: The econometric analysis revealed that joint auditing techniques explain 84.6% of variations in electronic audit report quality (R²=0.846), with audit committee expertise, meeting frequency, and technological integration demonstrating statistically significant positive impacts on report quality dimensions including relevance, reliability, comparability, and consistency. Novelty: This study uniquely applies autoregressive distributed lag modeling to demonstrate the long-term equilibrium relationship between joint auditing variables and electronic report quality in a supreme audit institution context, providing quantitative evidence of technological environment integration effects. Implications: Findings support regulatory frameworks promoting mandatory joint auditing adoption in financial institutions and emphasize the necessity of establishing professional institutes to govern joint audit practices while integrating continuous technological training for audit quality enhancement.Keywords : Joint Auditing, Technological Environment, Audit Report Quality, Electronic Reporting, Financial Statement AuditHighlight : Joint auditing enhances auditor independence and strengthens ability to detect fraud and errors effectively. Electronic reporting systems separate format design from execution across different software versions. Audit committee expertise increases electronic report quality by 1.13% per percentage point improvement.